Public Sector Employment and Compensation : An Assessment Framework - World Bank (World Bank, Washington, DC, 2021)
This paper aims to provide a framework for conducting public sector employment and compensation assessments that can help develop evidence-based reforms. Such a framework is necessary given growing debt distress and the need for greater expenditure efficiency in many of the World Bank’s client countries, and also due to the urgency for addressing global challenges like pandemics, climate change, building human capital, and reducing inequality, all of which require a strong role for the public sector.